The Effect of Solid Rate on Cyclones Pressure Drop and Erosion Rate at Coal Boiler Plant Using Computational Fluid Dynamics - Brario Anindito; Tantular Nurtono; Sugeng Winardi (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
Gas-solid separation systems with turbulent swirl flow that occur inside the cyclone will cause pressure drop and erosion on the cyclone wall. Both of these can cause a decrease in performance and increase maintenance costs for cyclones. CFD simulation is carried out on the actual cyclone dimensions used in the coal boiler industry. It was performed using the Reynolds Stress Model (RSM) for turbulent flow in the gas phase and Oka erosion model for its erosion model. The inlet velocity is fixed 6 m/s with variations in the solid rate ranged from 30 to 40 kg/s. This study will analyze the pressure drop and erosion rate on the cyclone walls in various solid rate variations. The simulation results show that the higher the solid rate with the same speed will reduce the pressure drop by 4% and at selected local area, increase the erosion rate on the cyclone wall by about 19%